A critical review of whole theory: Stationenlernen learning technique and German language learning outcomes - Eldaa Crystle Wenno; Kalvin Karuna; Henderika Serpara (Journal of Education and Learning (EduLearn), 2022)
This critical review aims to describe the integrity of paraphrasing the theory or references and scientific journals that become references. The contribution of this research is as a reference and input to develop the creativity of critical thinking of the quoters. The method used is listening and analyzing the journal's contents as a source of data; critically identifying the parts of the journal containing quotations, direct quotations, and paraphrasing of the theories being referenced. The results of the critical review show several weaknesses, including several quotes that are not accompanied by relevant data and references, errors in citing reference sources. In addition, quotations or paraphrases have paid attention to the integrity of meaning with several techniques, namely complete and partial paraphrasing techniques. Partial is divided into two; according to the research formulation, the theory is paraphrased and several points of the combined theory are paraphrased because they are closely related and complementary. This critical review implies that it is a follow-up study to analyze the advantages and disadvantages of a scientific article based on relevant theories, studies, and previous research results.